Clinical Experiences in the Treatment of Women with Breast Cancer and Comorbid Psychiatric Disorders - Braš, Marijana; Gregurek, Rudolf; Brajković, Lovorka; Lončar, Zoran; Erceg, Inja (2008)
PURPOSE: There is a high prevalence of different psychiatric disorders in women with breast cancer in different phases of their illness. The authors presented the one-year clinical experience in the assessment and treatment of psychiatric disorders and pain in the women with breast cancer. METHODS: The 25 women with breast cancer who were treated at the outpatient Clinic for psychological/psychiatric problems in women with breast cancer were selected as the sample of this study. On the base of medical records, interviews and different questionnaires (MMPI, COPE, Impact of Event Scale, Mc Gill Pain Questionnaire, STAI, Beck Depression Inventory, Quality of Life Questionnaire) the authors analyzed psychiatric comorbidity as well as different treatment methods that were used in their treatment. RESULTS: Women with breast cancer are found to experiencing mood and anxiety disorders, adjustment disorder, insomnia, behavioral problems and pain. Also, many of them had problems with body image and sexuality. Patients were treated with psychotropic drugs and psychotherapeutical interventions (individual and group psychodinamically oriented psychotherapy, family interventions). CONCLUSION: Psychiatric comorbidity in women with breast cancer is very complex and requires assessment and treatment individually tailored to the specific need of the patient. Early and accurate identification of psychiatric disorders improves access to appropriate care, reduces costs, and enhances treatment outcomes.
ENG